Acute Myocardial Infarction and its association with ABO blood group in Pakistani population - Imran Iftikhar , Hamid Sharif Khan , Adeel Ur Rehman (Journal of Rawalpindi Medical College, 2020)
OBJECTIVE: To determine the frequency of ABO blood groups among patients with acute myocardial infarction in the Pakistani population STUDY DESIGN: Cross-sectional study PLACE AND DURATION OF STUDY : Department of Interventional Cardiology, Rawalpindi Institute of Cardiology, Rawalpindi, from May 2015 to November 2015. METHODOLOGY: A total of 250 subjects with acute myocardial infarction were included in the study. The study was explained to the patients and informed consent taken. All patients underwent 12 lead electrocardiography using Mortara instrument ELI 250 and were analyzed by a single trained reader unaware of the patients’ blood group. Cardiac troponin levels were assessed at least three hours after the onset of symptoms. The ABO blood group was assessed by using the standard slide agglutination method in the hospital pathology laboratory and verified by the principal investigator. The data was collected on a pre-tested questionnaire by the investigator after taking informed consent from the patient. RESULTS: In our study, the mean age of patients was 57.3 years. 36.4% were between 18-50 years of age while 63.6%were between 51-80 years of age. 79.2% were male and 20.8% were females. Frequency of ABO blood groups among patients with acute myocardial infarction in our study population was recorded as 28.8% with O +ve , 26% with B+ve, 18.4% with A+ve, 13.2% with AB +ve, 5.6% with A-ve, 4.4% with B-ve, 3.2% with O-ve and 0.4% with AB -ve CONCLUSION: We concluded that the frequency of acute myocardial infarction in our population is higher among patients having blood group O+ve followed by B+ve blood group.